Do discurso sobre natureza à natureza do discurso: o caso do parlamento das águas - Espinoza, Rodrigo de Freitas (2011)
This dissertation addresses some of the ways which the environmental issue relates to certain standards of economic rationality and the construction of scientific-technical discourse. Its central objective is to discuss a form of sociological interpretation about the social hierarchies produced in the Basin Committees, emphasizing the fundamentals of these discourses and discursive modalities under construction and / or consolidated in this decentralized space of environmental governance. The empirical study is the region of the Basin Committee Tietê- Jacaré, located in the central region of São Paulo. It is the 13th State Committee who, like others, is structured by a tripartite management, State, Municipal and Civil Society. Each segment has 12 representatives who compose the Committee on equal and shall be established in a deliberative power over the management of Basin waters. The works used for analytical investigation are: Boaventura de Souza Santos and Enrique Leff in relation to the discussion of the concepts of economic rationality and scientific episteme and also the work of Pierre Bourdieu and Michel Foucault to conduct a research about social distinction on the water management.